2018
DOI: 10.1002/ieam.4069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of offshore oil exploration and development in the Alaskan Beaufort Sea: A three‐decade record for sediment metals

Abstract: Impacts from oil exploration, development, and production in the Beaufort Sea, Alaska, USA are assessed using concentrations of metals in sediments collected during 2014 to 2015, combined with a large data set for 1985 to 2006. Concentrations of 7 (1980s) or 17 (1999-2015) metals in 423 surface sediments from 134 stations, plus 563 samples from 30 cores were highly variable, primarily as a function of sediment granulometry with naturally greater metals concentrations in fine-grained, Al-rich sediment. Metals v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It has been widely reported that petroleum pollution is often accompanied by heavy‐metal pollution, and its existence usually affects the metabolic activity of microorganisms, which adversely affects the biodegradation of petroleum pollution [9,10]. Genes which are related to heavy‐metal resistance and biofilm were also observed in genome of JSTW, including pco A encoding copper resistance protein A, cop A encoding copper‐exporting P‐type ATPase, cop B encoding copper resistance protein B, cop C encoding copper‐binding protein, cop Z encoding copper chaperone, cus A encoding Cu/Ag efflux pump, cus F encoding periplasmic Cu and Ag efflux proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely reported that petroleum pollution is often accompanied by heavy‐metal pollution, and its existence usually affects the metabolic activity of microorganisms, which adversely affects the biodegradation of petroleum pollution [9,10]. Genes which are related to heavy‐metal resistance and biofilm were also observed in genome of JSTW, including pco A encoding copper resistance protein A, cop A encoding copper‐exporting P‐type ATPase, cop B encoding copper resistance protein B, cop C encoding copper‐binding protein, cop Z encoding copper chaperone, cus A encoding Cu/Ag efflux pump, cus F encoding periplasmic Cu and Ag efflux proteins.…”
Section: Resultsmentioning
confidence: 99%
“…However, petroleum hydrocarbons pollution is naturally associated with heavy‐metal pollution [9]. For instance, heavy metal pollution such as Cd, Cu, Ni and Cr have been revealed to usually coexists with petroleum pollution [10].…”
Section: Introductionmentioning
confidence: 99%